Community Participation In Buddhist-Based Educational Management - รัตนคร สมบัติ (Journal of Educational Review Faculty of Education in MCU, 2018)
Aparihaniya Dhamma is to prevent deterioration and lead to prosperity. To hold regular meetings and to meet together in harmony, disperse in harmony and do the business and duties of the Order in harmony are powerful. According to the National Education Act B.E. 2542, all sectors of society; individuals, families, communities, organizations, communities, local governments, priv ate organizations, professional organizations, religious organizations and other social institutions, have the rights in managing education. This system can strengthen the community by community learning process to let community in study, management and training in accordance with the need of community. By this way, the community learning process can be improved effectively.